Neural activity patterns stabilize during wakefulness and conscious experience. - Simon van Gaal (PLoS Biology)
Several neuronal markers have been proposed to differentiate the global brain states that underly states of consciousness. A new pre-registered study in PLOS Biology compares neural markers of loss of consciousness in flies when awake, asleep, and anesthetized.